Professionalism, Attractive Appearance, Real-Time Interaction, and Price Discounts on Purchase Intention during Live Streaming on TikTok - Yanti, Febri (Student Journal of Business and Management, 2024)
The purpose of this study is to analyze the effect of professionalism, attractive appearance, real time interaction, and Price Discounts on Purchase Intention. The research method is quantitative using primary data obtained from distributing online questionnaires.This study uses a quantitative method based on the philoshophy of positivism. The population in study is focused on users of the Tiktok application wherever they are but Indonesian citizens, while the sampling technique in this study is non-probability sampling. The questionnaire obtained 190 respondents who had criteria. 1) 17-30 years old, 2) respondents who have watched live streaming of product sales by live streamers on the Tiktok application. The analytical method in this study using SPSS 25.0 for windows was used to process and analyze data. The results of the study show that 1) professionalism has a positive and significant effect on Purchase Intention, meaning that the greater the positive reaction of individuals who have the intention to buy a product during Tiktok live streaming, the individual's Purchase Intention will also increase. 2) attractive appearance has a positive and significant effect on Purchase Intention, so the Purchase Intention of individuals who have the intention to buy products during Tiktok live streaming will also increase. 3) Real time interaction has a positive and significant effect on Purchase Intention. 4) The Price Discount has a positive and significant effect on Purchase Intention, meaning that the greater the discount given to consumers, the greater the Purchase Intention that arises when consumers see product sales while live streaming at the Tiktok shop. Suggestions for further research are expected to add other variables that are considered to have a significant influence on the dependent variable and explain the dependent variable. In addition, it is expected to expand the research population of all Tiktok users in Indonesia. The limitations in this study were in collecting data using a questionnaire because the answers given by respondents sometimes did not show the actual situation